Pengembangan Media Video Animasi Pembelajaran Berbasis OBS Studio dan LoomieLive Pada Mata Pelajaran Agama - Dwipangga, Rangga; Andri S, Mamok (Jurnal Penelitian Multidisiplin Ilmu, 2024)
The development of animated learning video media based on OBS Studio and Loomie Live for Religion subjects at SDN 167 Mengger Girang aims to develop interesting and effective learning media. This research uses the Research and Development (R&D) method with stages: 1) Needs analysis, 2) Designing media, 3) Creating media, 4) Implementation, and 5) Evaluation. The research results show that: 1) The development of animated learning video media based on OBS Studio and Loomie Live begins with analyzing potential and problems, collecting data and materials, designing scripts and products, testing, revising, validating, implementing and evaluating. 2) The effectiveness of animated learning video media based on material expert assessment reached 81.3% with the appropriate category, and there was an increase in student learning outcomes after using this media (t count = 11.054 ? t table = 2.119). Thus, animated learning video media based on OBS Studio and Loomie Live are effectively used in Religion subjects at SDN 167 Mengger Girang.